Pengentasan Kemiskinan Melalui Graduasi Sejahtera Mandiri Program Keluarga Harapan (PKH) di Indonesia : Tinjauan Sistematik - Muhammad Yusril Indra Syahputra; Oman Sukmana (STIKes Ibnu Sina Ajibarang, 2025)
Poverty remains one of the main problems in Indonesia that affects various aspects of people's lives. This study analyses poverty alleviation through the Family Hope Program (PKH) with a graduation approach towards independent prosperity. Through a systematic review of 17 journals from 2020 to 2024, it was found that PKH plays an important role in improving the welfare of poor families, especially in access to education and health. While the programme has shown positive results, significant challenges remain, such as economic dependency and limited access to basic services. Factors such as social capital, community support and the role of PKH facilitators prove crucial in achieving self-sufficient graduation. The results of this study suggest the need for a more holistic approach to empower beneficiary families to become more economically independent.